Burnout among Polish paramedics: insights from the Oldenburg Burnout Inventory - Kosydar-Bochenek, Justyna; Religa, Dorota; Iwanicka, Kamila; Szczupak, Mateusz; Krupa-Nurcek, Sabina (Frontiers in Public Health, 2024)
Introduction Emergency medical services rely heavily on paramedics who, as frontline responders, face unique stressors that can potentially lead to burnout. This pilot study utilizes the Oldenburg Burnout Inventory (OLBI) to assess burnout levels among Polish paramedics. The aim is to contribute to the understanding of burnout in this specific professional context and identify key factors influencing burnout dimensions. Future research will build on these preliminary findings. Materials and methods A cross-sectional study was conducted from March 01 to April 30, 2023, utilizing an online survey accessible to Polish paramedics. The OLBI, a validated tool, was employed to measure burnout, focusing on two dimensions: exhaustion and withdrawal of involvement. Results Among the 147 participating paramedics, the majority were male (65.99%). Paramedics exhibited burnout symptoms across both dimensions measured by The Oldenburg Burnout Inventory scale (OLBI), with an average level for lack of commitment recorded at 20.09, an average level for exhaustion at 20.60. The study revealed that 41.5% of paramedics experienced low burnout, 44.9% reported moderate burnout, and 13.6% faced high burnout risks. Analysis showed that women experienced significantly higher levels of exhaustion compared to men (p = 0.01). Conclusion This pilot study provides valuable initial insights into burnout among Polish paramedics. The OLBI’s two-factor structure, evaluating exhaustion and disengagement, proved reliable and valid in this context. The prevalence of burnout, with over 60% of paramedics experiencing moderate to high levels, highlights the urgency of addressing burnout in this profession. Future research will be essential to explore the underlying causes and develop targeted interventions. Practical implications Understanding the factors contributing to burnout among paramedics is crucial for developing targeted interventions. Strategies should focus on stress management training, organizational support, and well-being initiatives. Addressing gender-specific differences in burnout experiences is essential for tailoring interventions effectively. Proactive psychological support mechanisms and optimized working conditions can enhance paramedics’ overall well-being, ensuring their continued effectiveness in providing emergency medical services.